From mass consumer society to a society of consumers: Consumption and the experience of community in late modernity. Issue 4 (8th August 2017) - Colling, Matthew R.; Stovall, Josh; Flaherty, Jeremy; Cope, Michael R.; Brown, Ralph B.
Abstract: Many scholars argue that consumption of goods and services has eclipsed the local community as the locus of contact between the individual and society. Residents of two Mississippi Delta communities, in 1996 and again in 2007, were asked how often they shopped for consumable items outside of their communities. Logistic regression demonstrates a significant interaction effect between year and outshopping such that outshopping was positively associated with community sentiment in 1996 but not in 2007. These results may reflect larger shifts in society, as the function which community traditionally served – an access point to society – may have been replaced by hyper-individualized consumption. Such a transformation in consumption habits is adequately explained by the effects which globalization has had on rural residents' consumption habits. Arguably, peoples' contact point with society has shifted from its once solid-modern and genuine community footings to its present "liquid" and unstable simulacra of community.